Modal beam splitter: determination of the transversal components of an electromagnetic light field - Michael Mazilu (Scientific Reports, 2017)
Abstract The transversal profile of beams can always be defined as a superposition of orthogonal fields, such as optical eigenmodes. Here, we describe a generic method to separate the individual components in a laser beam and map each mode onto its designated detector with low crosstalk. We demonstrate this with the decomposition into Laguerre-Gaussian beams and introduce a distribution over the integer numbers corresponding to the discrete orbital and radial momentum components of the light field. The method is based on determining an eigenmask filter transforming the incident optical eigenmodes to position eigenmodes enabling the detection of the state of the light field using single detectors while minimizing cross talk with respect to the set of filter masks considered.